Pengaruh Brand, Citra Merek, dan Kualitas Produk terhadap Keputusan Pembelian Produk Scarlett pada Mahasiswi Fakultas Administrasi Bisnis di Kampus STIA Kota Bengkulu - Putra, M. Bima Eka; Gustini (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
This research aims to find out how the brand, brand image and product quality influence the decision to purchase Scarlett products among female students of the Faculty of Business Administration at the STIA campus in Bengkulu City. This type of research uses a quantitative approach, namely research that is processed using statistical methods, with a comparative type of research. The data collection technique used in this research is a questionnaire using a Likert scale. The analysis technique in this research is multiple linear regression analysis. The research results show that H1) there is a partially significant positive influence between brand equity on purchasing decisions for Scarlett Whitening products. H2) found that there is a partial positive and significant influence between product quality on purchasing decisions for Scarlett Whitening products Keywords: Brand, Image, Brand, Product Quality, Purchase Decision Scarlett, STIA Bengkulu